Intensive science and virtual philosophy - DeLanda, Manuel (London Continuum, 2002)
Deleuze is now regarded as the most radical andinfluential of contemporary philosophers. HereManuel DeLanda makes sense of Deleuze for bothanalytic and continental thought, for both scienceand philosophy